2018
DOI: 10.1016/j.ebiom.2018.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid A targeting the transgelin-actin complex to enhance vasoconstriction

Abstract: BackgroundSalvia miltiorrhiza is used extensively to treat cardiovascular diseases. SAA is a major bioactive component in Salvia miltiorrhiza and mediates myocardial ischemia (MI). However, the industrial production of SAA is limited due to low yields. In addition, the direct targets of SAA are unknown. Here we explore cardioprotective mechanisms and targets of SAA in the cardiovascular system.MethodsTransgelin and actin were identified as targets of SAA using a chemical biology method and were validated by Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Histological studies of human coronary arteries suggest that areas prone to atherosclerotic lesions contain more vascular SMCs, while areas less prone to atherosclerotic lesions have fewer vascular SMCs [ 4 – 6 ]. Therefore, understanding the relationship between VSMCs and AS may have important implications for the formulation of effective prevention and control measures for AS [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies of human coronary arteries suggest that areas prone to atherosclerotic lesions contain more vascular SMCs, while areas less prone to atherosclerotic lesions have fewer vascular SMCs [ 4 – 6 ]. Therefore, understanding the relationship between VSMCs and AS may have important implications for the formulation of effective prevention and control measures for AS [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAGLN, a member of the calmodulin family, acts as an actin-binding protein that regulates cytoskeletal remodeling by promoting actin aggregation 15 . The cellular immunofluorescence experiments and SEM showed that COMP could interact with TAGLN to regulate cell remodeling and promote EMT in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Transgelin (TAGLN) is an actin-binding protein that regulates the dynamics of the actin cytoskeleton and promotes the aggregation of G-actin to F-actin 14 . Our previous studies have shown that excited TAGLN-actin regulates the cytoskeleton and promotes cell contraction 15 . TAGLN is recognized as a tumor suppressor in the early stage 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…MST is a validated, robust method for measuring K d 's in solution based on molecular motion induced by an applied temperature gradient (Jerabek-Willemsen et al, 2011). Several studies have compared affinity measurements by MST and Surface Plasmon Resonance (SPR) and found them to be identical (Wang et al, 2016); (Zhong et al, 2018) Table 1 presents the affinities measured with the MST and SPA for K-Ras WT and three K-Ras mutants.…”
Section: Gtp Affinity To Wild-type K-ras and Three K-ras Mutantsmentioning
confidence: 99%